STREAMING SPEECH TO TEXT ON ANDROID A SOCKET.IO BASED SERVER APPROACH FOR ANDROID MOBILE APPLICATION - Nugroho, Douglas Rakasiwi; Limawan, Christopher; Kelvin (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This paper details a robust system enabling real-time Speech-to-Text capabilities on Android devices, leveraging a Socket.IO-based server architecture to manage audio streams and integrate with advanced language models. This approach effectively addresses the inherent challenges of on-device processing, such as latency, power consumption, and computational overhead, by offloading the intensive Speech-to-Text and Natural Language Processing tasks to a scalable server infrastructure. This distributed processing paradigm ensures minimal resource drain on the client device while maximizing accuracy and responsiveness.